A Study of Lithosphere–Ionosphere Seismic Precursors from Detecting Gamma-Ray and Total Electron Content Anomalies Prior to the 2018 ML6.2 Hualien Earthquake in Eastern Taiwan - Ching-Chou Fu; Hau-Kun Jhuang; Yi-Ying Ho; Tsung-Che Tsai; Lou-Chuang Lee; Cheng-Horng Lin; Ching-Ren Lin; Vivek Walia; I-Te Lee (Remote Sensing)
This study conducts a comprehensive analysis of observations related to the ML6.2 Hualien earthquake that struck eastern Taiwan on 6 February 2018, focusing particularly on gamma-ray emissions and total electron content (TEC) as earthquake precursors. Prior research has shown that significant gamma-ray enhancements are frequently detected at the YMSG (Yangmingshan gamma-ray) station prior to major earthquakes in eastern and northeastern Taiwan, suggesting that gamma-ray anomalies may serve as reliable indicators for identifying seismic precursors in this area. Our findings reveal a significant rise in gamma-ray emissions at the YMSG station from 19 January to 4 February 2018, which corresponds to a precursor period of approximately 18 days before the Hualien earthquake. Positive and negative TEC anomalies were observed in Taiwan on 20–21 January and 5 February, respectively, and may be considered as ionospheric precursors to the earthquake. Additionally, deep-learning techniques applied to TEC data facilitate the detection of ionospheric precursors associated with the Hualien earthquake, enabling forecasts of an approaching seismic event. Collectively, these observations indicate that all identified anomalies are regarded as short-term precursors, explicable through the theoretical framework of lithosphere–ionosphere coupling (LIC).